Anesthetic management of superior vena cava syndrome due to anterior mediastinal mass - Chaudhary, Kapil (Medknow Publications & Media Pvt Ltd, 2012)
Anesthetic management of superior vena cava syndrome carries a possible risk of life-threatening complications such as cardiovascular collapse and complete airway obstruction during anesthesia. Superior vena cava syndrome results from the enlargement of a mediastinal mass and consequent compression of mediastinal structures resulting in impaired blood flow from superior vena cava to the right atrium and venous congestion of face and upper extremity. We report the successful anesthetic management of a 42-year-old man with superior vena cava syndrome posted for cervical lymph node biopsy.